1996
DOI: 10.1002/(sici)1097-0142(19960901)78:5<1114::aid-cncr23>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of advanced medullary thyroid carcinoma with a combination of recombinant interferon α-2b and octreotide

Abstract: The combination of octreotide and interferon is well tolerated and can be recommended for the treatment of advanced MTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 28 publications
0
27
0
2
Order By: Relevance
“…In fact, the response to the therapy of bone metastases through surgery (Schlumberger, 1998), radioiodine (Marcocci et al, 1989;Maxon and Smith, 1990;Proye et al, 1992), external irradiation (Tubiana et al, 1985), chemotherapy (Grebe and Hay, 1995;Schlumberger, 1998) and biological therapy (Lupoli et al, 1996;Vitale et al, 2000) is poor in thyroid cancer patients.…”
mentioning
confidence: 99%
“…In fact, the response to the therapy of bone metastases through surgery (Schlumberger, 1998), radioiodine (Marcocci et al, 1989;Maxon and Smith, 1990;Proye et al, 1992), external irradiation (Tubiana et al, 1985), chemotherapy (Grebe and Hay, 1995;Schlumberger, 1998) and biological therapy (Lupoli et al, 1996;Vitale et al, 2000) is poor in thyroid cancer patients.…”
mentioning
confidence: 99%
“…Radiotherapy and chemotherapy play a marginal role in advanced MTC (Vitale et al 2001. Somatostatin analogues are able to control the neuroendocrine symptoms induced by advanced MTC (Lupoli et al 1996, Vitale et al 2000. In recent years, several tyrosine kinase inhibitors (axitinib, cabozantinib, gefitinib, imatinib, motesanib, sorafenib, sunitinib and vandetanib) have been evaluated in phase I, II and III clinical trials of patients with advanced MTC.…”
Section: :1mentioning
confidence: 99%
“…In patients with advanced metastatic disease, the administration of octreotide combined with interferon was studied; in a study of 8 patients with advanced MTC, patients received octreotide (at a starting dose of 150g/day sc for 6 months, followed by a dose of 300g/day sc for another 6 months) combined with rIFN-alpha-2b (at a dose of 5 million IU/day im 3 times a week, for 12 months) (Lupoli et al, 1996); while significant symptomatic improvement was observed in some of the treated patients (diarrhoea, in four patients, and flushing, in one), no significant changes in the size of metastases were observed. A maximum decrease of calcitonin was reached after 3 months in 4 patients, while in all patients the CEA levels decreased during treatment.…”
Section: Page 19 Of 43mentioning
confidence: 99%